Penerapan Model Project Based Learning untuk Meningkatan Kinerja dan Prestasi Belajar Fisika Siswa SMK - Mulyadi, Eko (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
This study aims at improving the students’ performance and achievement in grade XI AV1 of SMK Negeri 3 Yogyakarta with the application of Project Based Learning in Physics learning for Static Electricity and Direct Current Electricity competencies. This study used a classroom action research approach implementing two cycles. Every cycle consisted of planning, action, observation and reflection. The PjBL included the steps of determining, planning, scheduling, monitoring, presentation and evaluation. The aspects of the achievement were measured by a pre-test, a product assessment, and a post-test. The results showed that the application of PjBL improved the performance up to 18.75% and improved the achievement 15.70 and 24.63 for the first cycle and the second cycle respectively.